Deskripsi Manajemen Sumber Daya Manusia Laboratorium Biologi SMA di Kota Yogyakarta - Safitri, Novita Ramadhani; Ikrima, Zalfa; Salsabilla, Farah; Insra, Atala Rania; Saifuddin, Much Fuad; Puspitasari, Etika Dyah (BIOEDUKASI (Jurnal Pendidikan Biologi), 2024)
Laboratory management is an integral part of laboratory activities related to human resources and professional staff who manage skillfully in a combination of management and laboratory equipment. This study aims to describe the management of human resources in the biology laboratory of Senior High School in Yogyakarta City by looking at the achievement of its duties, which are adjusted to the Regulation of the Minister of National Education No. 26 of 2008 in supporting the laboratory management of School A, School B, and School C. This study used descriptive analysis with a qualitative approach. The data analysis technique in this research is using descriptive analysis of interview results. The research results from the three schools were insufficient to meet the standards of school laboratory personnel, because there was still a shortage of laboratory personnel that should be needed. The competencies listed in the Regulation of the Minister of National Education No. 26 of 2008 of the three schools have been implemented.